Dynamic Systems, Economic Growth, and the Environment - Crespo Cuaresma, Jesús.; Crespo Cuaresma, Jesús.; Palokangas, Tapio.; Palokangas, Tapio.; Tarasyev, Alexander.; Tarasyev, Alexander. (Dynamic Modeling and Econometrics in Economics and Finance, 2010)
The book focuses on the sustainability of economic growth in a changing environment, under the effects of global warming, dwindling energy resources, and technological change. It also provides explanations for significant fluctuations in countries’ growth rates. The results are derived from historical evidence on economic growth in relation to environmental policy, technological change, development of transport infrastructure, population issues, and environmental mortality. The rigorous analysis of theoretical and applied aspects reveals important policy implications for optimal investment, optimal timing of abatement activities, and for an optimal balancing of economic growth with environmental concerns.